A Methods engineering study of Temprite Industrial Corporation - Azada, Benjamin (College of Engineering, 1994)
This study was made on Temprite Industrial Corporation in view of the need to develop an efficient system of operations in the factory, and to simplify and standardize office procedures. Through the utilization of the techniques of Methods Study and Systems and Procedures Study, the present ways of doing work in the factory and in the office of Temprite Industrial Corporation were systematically recorded and critically examined. Proposals in the following key areas were developed to increase the efficiency of operations : 1. Production process -- eliminate operation wherein excess silicone is removed; reposition on/off switches of the spotwelder and the pneumatic presses; change work methods to economize of human effort; 2. Plant layout -- move grinding wheel beside boring machine; move cooling table near testing board; procure additional table for temporary storage beside testing board; use area near generator to store work-in process; paint gangways; change arrangement of various workstations; 3. Office procedures -- change design of Finished Goods Releasing Record; design pre-printed Order Slips; 4. Materials handling facilities -- rationalize use of drums and crates; instructs workers to place all crates and work-in-process near generator; 5. Working conditions and environment -- procure seats with backrests for workers; elevate rack by 5 inches; post job instruction sheets at workstations; fix electricals; conduct periodic inspection and cleaning; improve lighting; fit industrial fans with fanguards; procure personal protective equipment. All these improvements can be implemented within a period of one month; and require minimal capital outlay.